Daños en plantas de un sotobosque tropiéal premontano pluvial, Costa Rica - Di Stéfano G, José Fco (Universidad de Costa Rica, 1996)
Damage (visually categorized) was studied during the rainy season in woody vegetation less than 8 m tall (n=230) in 22 circular (radius= 1 m) plots rarndomly spread over one hectare of primary premontane tropical rain forest (San Ramón. Costa Rica). About half of tho individuals were 0.11-0.5 m tall, and nearly 85% of them were damaged by insects. Severity and number of injury types increased in tite tallest plants. Almost half of the individuals less than 0.1 m tall. appeared undamaged. Physical damage occurred in about 6.5% of the plants.